Revision der palaearktischen Arten der Gattung Lasiopa Brullé, 1832 (Diptera: Stratiomyidae). - Dušek, Jindřich; Rozkošny, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1970)
In their revision of the palaearctic species of the genus Lasiopa Brullé the authors describe a new species: Lasiopa tsacasi spec. nov., and a new subspecies: Lasiopa peleteria albanica sspec. nov. The species Lasiopa obscura Tsacas is synonymized with Lasiopa krkensis Lindner. On the basis of further taxonomic characteristics disregarded in previous publications, as the male hypopygia, the form of the antennae and others, the previously described taxa and the new taxa can be reliably distinguished. The comparative relations between the various species of the genus are characterized which form rather distinct groups consisting of two or three species. These groups, however, cannot be regarded as idependent subgenera. Apart from these there are two isolated species. All characteristics recorded for the first time are shown in illustrations. Nomenclatural Actsobscura Tsacas, 1963 (Lasiopa), syn. n. of Lasiopa krkensis Lindner, 1938tsacasi Dušek & Rozkošný, 1970 (Lasiopa), spec. n.albanica Dušek & Rozkošný, 1970 (Lasiopa peleteria), sspec. n.